دور مواقع التواصل الاجتماعي في انتشار السلوك الاستهلاكي التفاخري لدى البنات - ثوانسة, إكرام; ضيف, جيهان (جامعة الوادي - University of Eloued, 2023)
هدفت هذه الدراسة وبشكل أساسي للتعرف على أثر مواقع التواصل الاجتماعي في نشر السلوك الاستهلاكي التفاخري لدى الطالبات، كما حاولت الإجابة على التساؤلات الفرعية: - هل للنظام الاجتماعي دور في التأثير على السلوك الاستهلاكي لدى طالبات علوم الإعلام والاتصال؟ - هل يسهل تبني سلوكيات استهلاكية جديدة بالنسبة لطالبات الإعلام والاتصال؟ - هل تؤثر العادات الاستهلاكية الجديدة المتبناة من مواقع التواصل الاجتماعي على الجانب المادي لدى طالبات الإعلام والاتصال؟ استخدمت الدراسة المنهج الوصفي كما اعتمدنا على أداة جمع البيانات التالية: الملاحظة، والاستمارة وقسمت الإستمارة إلى أربع محاور: البيانات الشخصية، ظروف التعرض لمواقع التواصل الاجتماعي، دور النظام الاجتماعي في التأثير على السلوك الاستهلاكي لدى طالبات علوم الإعلام والاتصال، تبني سلوكيات استهلاكية جديدة بنسبة لطالبات الإعلام والاتصال، حيث بلغ عدد أفراد العينة 100 فرد من طالبات علوم الإعلام والاتصال بجامعة الشهيد حمه لخضر بالوادي، لتتوصل الدراسة في الأخير إلى مجموعة من النتائج أبرزها: - أن موقعا الفيس بوك والانستغرام الأكثر تصفحا لدى طالبات علوم الاعلام والاتصال وذلك راجع للفئة العمرية للطالبات التي تتراوح معظمها ما بين 19 الى 30 سنة. - أن أهم عامل من عوامل ممارسة السلوك الاستهلاكي هو عامل الحاجة إلى التقدير والتي تتمثل في رغبة الفرد في للوصول إلى وضعية متميزة في المجتمع، لتفادي الطبقات والصفات بين أفراد المجتمع أي تغطي كامل النقائص لديها. - أن مواقع التواصل الاجتماعي لها دور كبير في نشر السلوك الاستهلاكي لدى الطالبات، وذلك من خلال المحتوى المعروض الذي يؤثر فعليا في شخصية المتلقي وقد يكون الأثر على المدى القريب أو البعيد. The main objective of this study was to examine the impact of social media platforms on the consumption behavior of female students, particularly focusing on conspicuous consumption. The study aimed to answer the following sub-questions: - Does the social system play a role in influencing the consumption behavior of students majoring in media and communication sciences? - Does it facilitate the adoption of new consumption behaviors among media and communication students? - Do the newly adopted consumption habits from social media platforms affect the material aspect of media and communication students? The study employed a descriptive methodology and utilized the following data collection tools: observation and a questionnaire. The questionnaire was divided into four sections: personal data, exposure to social media platforms, the role of the social system in influencing consumption behavior among media and communication students, and the adoption of new consumption behaviors among media and communication students. The sample size consisted of 100 female students majoring in media and communication sciences at Hamah Lakhder University in EL-OUED.In conclusion, the study arrived at several results, including: - The Facebook and Instagram sites are the most visited by media and communication science students, and this is due to the age group of the students, most of whom range from 19 to 30 years. - That the most important factor in the practice of consumer behavior is the factor of the need for appreciation, which is represented in the desire of the individual to reach a privileged position in society, to avoid the classes and qualities among the members of society, i.e. covering all its deficiencies. - That social networking sites have a major role in spreading consumer behavior among female students, through the displayed content that actually affects the personality of the recipient, and the impact may be in the short or long term.
مذكرة ماستر إعلام وإتصال
Keywords: مواقع التواصل الاجتماعي، سلوك، طالبات، التفاخر، تأثير; social media platforms, behavior, students, conspicuous consumption, impact